Rabbitpox in New Zealand White Rabbits: A Therapeutic Model for Evaluation of Poxvirus Medical Countermeasures Under the FDA Animal Rule - Perry, Mark R.; Warren, Richard; Merchlinsky, Michael; Houchens, Christopher; Rogers, James V. (Frontiers in Cellular and Infection Microbiology, 2018)
The elimination of smallpox as an endemic disease and the obvious ethical problems with clinical challenge requires the efficacy evaluation of medical countermeasures against smallpox using the FDA Animal Rule. This approach requires the evaluation of antiviral efficacy in an animal model whose infection recapitulates the human disease sufficiently well enough to provide predictive value of countermeasure effectiveness. The narrow host range of variola virus meant that no other animal species was sufficiently susceptible to variola to manifest a disease with predictive value. To address this dilemma, the FDA, after a public forum with virologists in December 2011, suggested the development of two animal models infected with the cognate orthopoxvirus, intradermal infection of rabbits and intranasal infection of mice, to supplement the non-human primate models in use. In this manuscript, we describe the development of an intradermal challenge model of New Zealand White rabbits with rabbitpox virus (RPXV) for poxvirus countermeasure evaluation. Lethality of RPXV was demonstrated in both 9 and 16-weeks old rabbits with an LD50 < 10 PFU. The natural history of RPXV infection was documented in both ages of rabbits by monitoring the time to onset of abnormal values in clinical data at a lethal challenge of 300 PFU. All infected animals became viremic, developed a fever, exhibited weight loss, developed secondary lesions, and were euthanized after 7 or 8 days. The 16-weeks RPXV-infected animals exhibiting similar clinical signs with euthanasia applied about a day later than for 9-weeks old rabbits. For all animals, the first two unambiguous indicators of infection were detection of viral copies by quantitative polymerase chain reaction and fever at 2 and 3 days following challenge, respectively. These biomarkers provide clinically-relevant trigger(s) for initiating therapy. The major advantage for using 16-weeks NZW rabbits is that older rabbits were more robust and less subject to stress-induced death allowing more reproducible studies.